Ultra High-Speed CMOS Circuits Beyond 100 GHz - Gharavi, Sam.; Heydari, Babak; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The book covers the CMOS-based millimeter wave circuits and devices and presents methods and design techniques to use CMOS technology for circuits operating beyond 100 GHz. Coverage includes a detailed description of both active and passive devices, including modeling techniques and performance optimization. Various mm-wave circuit blocks are discussed, emphasizing their design distinctions from low-frequency design methodologies. This book also covers a device-oriented circuit design technique that is essential for ultra high speed circuits and gives some examples of device/circuit co-design that can be used for mm-wave technology. Offers a detailed description of high frequency device modeling from a circuit designer perspective; Presents a set of techniques for optimizing the performance of CMOS for mm-wave technology, including noise and low noise design for mm-wave; Introduces circuit/device co-design techniques. .
Introduction -- mm-wave Device Modeling -- mm-wave Device Optimization -- mm-wave CMOS Noise Analysis -- Unilateralization -- Terahertz CMOS Devices, Circuits and Systems -- Imaging Applications.
Keywords: Electronic circuits; Computer-aided engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design